De-excitations of highly excited 11B⁎ and 15N⁎ based on the GEMINI++ code - Yujie Niu; Wan-Lei Guo; Miao He; Jun Su (Physics Letters B)
Nuclear de-excitations associated with neutrino-nucleus interactions and nucleon decays are playing an increasingly significant role in neutrino experiments. We explore the GEMINI++ code and estimate its ability to account for the de-excitation processes of highly excited 11B⁎ and 15N⁎, which can be created in the liquid scintillator and water Cherenkov detectors respectively. It is found that GEMINI++ can not describe the nuclear experimental data of 11B⁎ and 15N⁎ well. To improve its performance for de-excitations of light nuclei, we modify GEMINI++ and then develop a code of GEMINI++4ν, which can give the best predictions compared with experimental measurements among some widely used statistical model codes.